2001
DOI: 10.1007/s100380170035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 197 genetic variations in six human methyltransferase genes in the Japanese population

Abstract: Methylation is an important event in the biotransformation pathway for many drugs and xenobiotic compounds. We screened DNA from 48 Japanese individuals for single-nucleotide polymorphisms (SNPs) in six methyltransferase (MT) genes (catechol-O-MT, COMT; guanidinoacetate N-MT, GAMT; histamine N-MT, HNMT; nicotinamide N-MT, NNMT; phosphatidylethanolamine N-MT, PEMT; and phenylethanolamine N-MT, PNMT) by direct sequencing of their entire genomic regions except for repetitive elements. This approach identified 190… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Both genes regulate brain dopaminergic transmission, and both polymorphisms are functional, in that they lead to differences in gene expression and/or protein function (13)(14)(15)(16)(17)(19)(20)(21)(22). Therefore, the effect of a given polymorphism on fronto-temporal cortical activation during a cognitive task may not be the same across individuals who carry different variants of a second polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both genes regulate brain dopaminergic transmission, and both polymorphisms are functional, in that they lead to differences in gene expression and/or protein function (13)(14)(15)(16)(17)(19)(20)(21)(22). Therefore, the effect of a given polymorphism on fronto-temporal cortical activation during a cognitive task may not be the same across individuals who carry different variants of a second polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic activity of COMT is altered by a guanine (G) to adenine (A) SNP change (known as Val158Met or rs4680) in the gene, which translates into a Val-to-Met amino acid change in codon 158 of the protein. This polymorphism is codominant and causes a 3-to 4-fold decrease in the molecular thermo-stability of the protein, which decreases its abundance and enzymatic activity, inclusively in the human brain (13)(14)(15)(16)(17). The DAT gene displays a polymorphic 40-bp variable number of tandem repeats (VNTR) in a UTR, which yields alleles ranging from 3 to 11 repeats, 9-and 10-repeat alleles being the most common (18).…”
mentioning
confidence: 99%
“…The majority of COMT and schizophrenia association studies (with some exceptions, generally mutation scans [22][23][24]30,73,[102][103][104] ) only assay for one variant, Val 108/158 Met. Three mutation scans of COMT have been carried out on collections of American (n ¼ 157), 102 Chinese (n ¼ 50), 104 and French (n ¼ 50) 103 schizophrenic subjects for a total of 514 scanned chromosomes, and six mutation scans have been performed on a total of 948 control chromosomes 25,61,102,[105][106][107] (Supplementary Table 1). Of the seven variants discovered in the COMT exons of schizophrenics, five are common and found in several schizophrenia and controls scans, one is common but only found in a scan on schizophrenics (although when directly assayed for in controls it was found at an equivalent frequency) 103 and one was rare and found only in one schizophrenic subject 102 (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…21 Extension of previously determined 13 COMT promoter sequence, coupled with functional deletion analyses of these promoter regions, showed that estrogen can specifically downregulate human COMT gene transcription in a time-and dose-dependent manner in the presence of estrogen receptors in an amount comparable to the gender difference in COMT activity in humans. 21 For the COMT distal promoter, the 323 bp region containing rs2097603 (called À287A/G by some authors [22][23][24] and À1217A/G by others 25,26 ) mediated this effect. 21 If higher COMT activity was a risk factor for schizophrenia (see Discussion below), or conversely, lower COMT activity was somewhat protective against schizophrenia, the 20-30% lower COMT activity in women [27][28][29] would be consistent with several observations with regard to gender differences in schizophrenia as suggested previously.…”
mentioning
confidence: 99%
“…Repetitive elements were excluded from the search by invoking the REPEAT MASKER computer program, in the manner described previously (Seki et al 2000). PCR reactions and DNA sequencing were carried out, as previously described (Saito et al 2001). The SNPs in this region were genotyped by means of Invader (Japanese samples) or Amplifluor assays (UK samples) (Bengra et al 2002), and VNTR loci were analyzed with respect to allele sizes using the Applied Biosystems ABI PRISM 3700 Automated DNA Sequencer and GeneScan software (GenoTyper program).…”
Section: Discovery Of Snps In the Tfap2b Gene And Genotypingmentioning
confidence: 99%